Solenoid Valve Control Design Using Arduino On Freshwater Generator Properties - Prasetyo, Aditya; Narto, Amad; Sujarman, Febria; utari, riyadini (LPPM AKMI SUAKA BAHARI CIREBON, 2023)
In the modern era of the maritime world, the learning process related to ship machinery is essential and crucial for students to master. So many effective learning methods are used, one of which is the learning method using machining aids on ships. Therefore, making ship machining aids is an exciting thing to work on in this modern era. The type of teaching aid made by the author is a solenoid valve controlled by Arduino on a freshwater generator teaching aid. The method used is research and development, a process or steps to develop a new product or improve an existing product, both hardware and software. The model in this development research is a procedural model, which outlines the manufacturing steps exposed sequentially and gradually from the beginning to the end. The solenoid valve control model by Arduino on the freshwater generator teaching aid utilizes two electronic modules: the Arduino Uno type module and the one-channel timer delay relay module. The two modules are programmed directly with the buttons on the module. The working system in this prop is that the heater is filled with water and then heated, and then the water vapor is flowed through the transfer pipe and condensed using a condensor and holding tank. This system can run because of the automation control system in the electronic module.